2016
DOI: 10.14720/aas.2016.107.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Impact of foliar application of nano micronutrient fertilizers and titanium dioxide nanoparticles on the growth and yield components of barley under supplemental irrigation

Abstract: Nano-fertilizers are new generation of the synthetic<em> </em>fertilizers which contain readily available nutrients in nano scale range. Nano fertilizers are preferred largely due to their efficiency and environment friendly nature compared to conventional<em> </em>chemical<em> </em>fertilizers. To evaluate the effects of foliar spray<em> </em>of micronutrient nano-fertilizer (iron and zinc) and nano-titanium dioxide (nTiO<sub>2</sub>) solution on gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 19 publications
(30 reference statements)
7
63
0
Order By: Relevance
“…It was found that, nanoanatase TiO 2 promotes antioxidant stress by decreasing the accumulation of superoxide radicals, hydrogen peroxide, and malonyl dialdehyde content while enhancing the activities of superoxide dismutase, catalase (ascorbate peroxidase), and guaiacol oxidase, thereby increasing the evolution oxygen rate in spinach chloroplasts under UV-B radiation (Lei et al, 2008).. Khot et al (2012) concluded that, the nano size of TiO 2 might have increased the absorption of inorganic nutrients, accelerated the breakdown of organic substances, and also caused quenching of oxygen free radicals formed during the photosynthetic process, hence increasing the photosynthetic rate. This finding supports our previous research which showed that foliar application of nTiO 2 on barley plants in a semi-arid region positively affected growth rate and seed yield (Janmohammadi et al, 2016a). It seems that, nTiO 2 plays a significant role in activatingdefense mechanism and modulating biosynthesis of phytohormones such as cytokinins and gibberellin (Mandeh et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…It was found that, nanoanatase TiO 2 promotes antioxidant stress by decreasing the accumulation of superoxide radicals, hydrogen peroxide, and malonyl dialdehyde content while enhancing the activities of superoxide dismutase, catalase (ascorbate peroxidase), and guaiacol oxidase, thereby increasing the evolution oxygen rate in spinach chloroplasts under UV-B radiation (Lei et al, 2008).. Khot et al (2012) concluded that, the nano size of TiO 2 might have increased the absorption of inorganic nutrients, accelerated the breakdown of organic substances, and also caused quenching of oxygen free radicals formed during the photosynthetic process, hence increasing the photosynthetic rate. This finding supports our previous research which showed that foliar application of nTiO 2 on barley plants in a semi-arid region positively affected growth rate and seed yield (Janmohammadi et al, 2016a). It seems that, nTiO 2 plays a significant role in activatingdefense mechanism and modulating biosynthesis of phytohormones such as cytokinins and gibberellin (Mandeh et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Results of this study showed that foliar application nano-fertilisers and nano beneficial particles significantly affected seed yield which corroborate the findings of a great deal of our previous work on barley under supplemental irrigation in semi-arid region (Janmohammadi et al 2016). The results of cluster analysis revealed that the effects of foliar treatments were different on cultivars.…”
Section: Discussionsupporting
confidence: 89%
“…The first factor was foliar treatment included control (check; no traetment), nano-chelated Fe (2,000 ppm), nano-chelated Zn (2,000 ppm), nano-Ti (20 ppm), nano-Si (20 ppm). The concentrations were selected according to the results of previous experiments in the region (Janmohammadi et al 2016;Janmohammadi et al 2017). The consumption rate was 100 cc/m 2 .…”
Section: Site Of Studymentioning
confidence: 99%
“…Nitrogen as one of the main nutrients in agricultural production, might be given only very few parts to plant and soil need, though reports stated that using very small nanofertilizer particles is more effective than this rate [45]. The researchers suggested that nano-fertilizers considerably influenced the straw yield and grain yield [46] …”
Section: Paddy Yieldmentioning
confidence: 99%